Angiopoietin-2 as a Marker of Retinopathy in Children and Adolescents With Sickle Cell Disease: Relation to Subclinical Atherosclerosis. Issue 5 (July 2019) - Andrawes, Nevine G.; Ismail, Eman A.; Roshdy, Maged M.; Ebeid, Fatma S.E.; Eissa, Deena S.; Ibrahim, Amna M.
Abstract : Objectives: Angiopoietin-2 (Ang-2) is a multifaceted cytokine that functions in both angiogenesis and inflammation. A proangiogenic state has been found in adults with sickle cell disease (SCD), mainly because of elevated Ang-2 levels. We determined Ang-2 level in 40 children and adolescents with SCD compared with 40 healthy controls and assessed its relation to retinopathy as well as carotid intimamedia thickness (CIMT). Methods: Hematologic profile, serum ferritin, and serum Ang-2 were measured. CIMT was assessed using high-resolution ultrasound. Fundus examination was performed followed by fundus fluorescein angiography. Optical coherence tomography angiography (OCTA) was used to find small vascular changes not clinically manifested. Results: Ang-2 levels and CIMT were significantly higher in SCD patients compared with controls. The incidence of nonproliferative retinopathy was 45%. SCD patients with retinopathy were older in age with a history of sickling crisis of >3 attacks per year and had a higher incidence of sickle cell anemia than sickle β-thalassemia. Ang-2 cutoff value 9000 pg/mL could significantly detect the presence of retinopathy among SCD patients with 100% sensitivity and specificity. Serum Ang-2 levels were positively correlated with HbS and CIMT. Logistic regression analysis revealed that Ang-2 and HbS significantly contribute to retinopathy among patients with SCD. Conclusions: Elevated Ang-2 highlights the role of angiogenesis in the pathophysiology of SCD and may be considered a promising marker for screening of patients at risk of sickle retinopathy and vascular dysfunction.